1996
DOI: 10.1111/j.1746-1561.1996.tb06252.x
|View full text |Cite
|
Sign up to set email alerts
|

A Profile of Rural Texas Adolescents Who Carry Handguns to School

Abstract: Students in randomly selected eighth and 10th grade English classrooms (n = 1,072) in central Texas schools were surveyed in fall 1994 regarding carrying weapons to school and associated risk factors. Students who carried a handgun to school one or more times during the preceding 12 months were compared to those who had not done so, using discriminant analysis and chi-square. Gun carrying at school increased 138% from seven years earlier in the same area using the same survey procedures. Most students reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
72
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 3 publications
7
72
2
Order By: Relevance
“…However, it has also been suggested that it is not so much being the initiator of aggression, rather it is being the target of aggression, that triggers weapon carrying as a defensive response [7,21]. Consistent with this perspective, weapon carrying has been associated with feelings of being threatened, such as victimization, fearfulness, and selfprotection [7,[21][22][23][24].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…However, it has also been suggested that it is not so much being the initiator of aggression, rather it is being the target of aggression, that triggers weapon carrying as a defensive response [7,21]. Consistent with this perspective, weapon carrying has been associated with feelings of being threatened, such as victimization, fearfulness, and selfprotection [7,[21][22][23][24].…”
mentioning
confidence: 97%
“…The latter two explanations may be interrelated: weapon carrying to enhance threats against others may increase the perceived need to carry weapons to deter or defend against potential retaliatory attacks; and weapon carrying for defensive purposes may embolden youth to take a more aggressive stance [23,[25][26][27]. Weapon carrying may therefore emerge as a complex interaction between adolescents' status as an initiator of aggression and their experience as a victim of aggression.…”
mentioning
confidence: 99%
“…Similarly, children and adolescents using drugs and/or alcohol are twice as likely to be in possession of a firearm, while 60% of students bringing a gun to school did so for protection or out of anger at another student (Furlong, Casas, Corral, Chung, & Bates, 1997). Finally, gun possession is greatest among children and adolescents who are exposed to guns in the home or community of origin (Kingery, Pruitt, & Heuberger, 1996), who reside in high-crime areas, witness domestic violence, or have experienced physical or sexual abuse (Furlong & Morrison, 1994).…”
Section: Gun Ownership Control Laws Accessibility and Acceptabilitymentioning
confidence: 99%
“…18 risk factors include gun-related victimization [19][20][21] and residing in unsafe neighborhoods. 22 We examine the association between participation in the illegal drug economy, gun-related victimization and gun carrying among young incarcerated men and women.…”
Section: Introductionmentioning
confidence: 99%